Hubungan Kecepatan dan Kekuatan Otot Tungkai dengan Ketepatan Shooting ke Arah Gawang Pada Mahasiswa Putra Semester 4A Pendidikan Kepelatihan Olahraga Universitas Riau - Ramadhoni, Syafridho Ramadhoni; Wijayanti, Ni Putu Nita Wijayanti Nita; ', Slamet (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study was conducted by using a correlation research design that aims to investigate how far the variables on a factor that is related to other factors. The data taken in this study are directly taken and data obtained from samples that have been set, the figures from the results of tests of speed and leg muscle strength with precision shooting toward the goal in the men’s half of the students 4A Sport Coaching Education University of Riau . Calculation of the correlation between speed (X1) with the results of shooting toward the goal (Y) using the product moment correlation formula. Testing criteria if r count> rtable, then there is a significant relationship, and vice versa (Sudjana 2006: 369). From the calculation of the correlation between speed with the results of shooting toward the goal r count -0,482 whereas r table at the level of at signification α = 0.05 is -0,456. Means in this case there is a relationship between speed with the result of shooting toward the goal. From the calculation of the correlation between leg muscle strenght (X2) with the result of shooting toward the goal (Y) obtained r count 0,627,whereas r table at the level of at signification α = 0.05 level is 0,456. Means in this case there is a relationship between leg muscle strenght with the result of shooting toward the goal,thus the better the speed and strenght of the muscles in the leg that had player the better the ball towards the opposing goal as did his thing shooting toward the goal.When speed and leg muscle strenght is not good,then the shooting is done right will not lead toward the goal as we expected. From the calculation of multiple correlation coefficient (R test) obtained R = 0.627 while rtabel count obtained for 0.456 so rhitung> rtable, meaning that there is a relationship together between speed (XI) and leg muscle strenght (X2) with result of shooting toeard the goal (Y). Keywords: Connection Speed and leg muscle strenght.